Anti‐lung Cancer Effects of Polyphyllin VI and VII Potentially Correlate with Apoptosis In Vitro and In Vivo. (13th August 2015) - Lin, Zhufen; Liu, Yuting; Li, Fangyuan; Wu, Jinjun; Zhang, Guiyu; Wang, Ying; Lu, Linlin; Liu, Zhongqiu
<x xml:space="preserve">Abstract</x> Polyphyllin VI (PVI) and polyphyllin VII (PVII) derived from Paris polyphylla possess anti‐cancer activities. However, the mechanisms for the anti‐lung cancer effects of PVI and PVII remain poorly understood. In this study, PVI and PVII exhibited inhibitory effects on the proliferation of A549 and NCI‐H1299 cells. PVI and PVII induced G2/M cell cycle arrest and triggered apoptosis. PVI and PVII upregulated the tumor suppressor protein p53 and downregulated cyclin B1. The two treatments significantly increased the expression levels of death receptor 3, death receptor 5, Fas, cleaved PARP, and cleaved caspase‐3. Furthermore, PVI and PVII significantly inhibited the growth of A549 cells in vivo. The tumor inhibitory rates of PVI were 25.74%, 34.62%, and 40.43% at 2, 3, and 4 mg/kg, respectively, and those of PVII were 25.63%, 41.71%, and 40.41% at 1, 2, and 3 mg/kg, respectively. Finally, PVI and PVII regulated the expression of proteins related to the apoptotic pathway in A549 xenografts. In summary, PVI and PVII exhibited strong inhibitory effects on lung cancer cell growth in vitro and in vivo by inducing G2/M cell cycle arrest and triggering apoptosis. Copyright © 2015 John Wiley & Sons, Ltd.